Hair analysis for long-term monitoring of buprenorphine intake in opiate withdrawal - Pirro, Valentina; Fusari, Ivana; Di Corcia, Daniele; Gerace, Enrico; De Vivo, Enrico; Salomone, Alberto; Vincenti, Marco (Therapeutic drug monitoring, 2014)
Buprenorphine (BUP) is a psychoactive pharmaceutical drug largely used to treat opiate addiction. Short-term therapeutic monitoring is supported by toxicological analysis of blood and urine samples, whereas long-term monitoring by means of hair analysis is rarely used. Aim of this work was to develop and validate a highly sensitive ultrahigh-performance liquid chromatography tandem mass spectrometry method to detect BUP and norbuprenorphine (NBUP) in head hair. Interindividual correlation between oral dosage of BUP and head hair concentration was investigated. Furthermore, an intra-individual study by means of segmental analysis was performed on subjects with variable maintenance dosage. Hair samples from a population of 79 patients in treatment for opiate addiction were analyzed. The validated ultrahigh-performance liquid chromatography tandem mass spectrometry protocol allowed to obtain limits of detection and quantification at 0.6 and 2.2 pg/mg for BUP and 5.0 and 17 pg/mg for NBUP, respectively. Validation criteria were satisfied, assuring selective analyte identification, high detection capability, and precise and accurate quantification. Significant positive correlation was found between constant oral BUP dosage (1-32 mg/d) and the summed up head hair concentrations of BUP and NBUP. Nevertheless, substantial interindividual variability limits the chance to predict the oral dosage taken by each subject from the measured concentrations in head hair. In contrast, strong correlation was observed in the results of intra-individual segmental analysis, which proved reliable to detect oral dosage variations during therapy. Remarkably, all hair samples yielded BUP concentrations higher than 10 pg/mg, even when the lowest dosage was administered. Thus, these results support the selection of 10 pg/mg as a cutoff value.